PENGARUH PERCEIVED QUALITY DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH DI TOKO MY LOVA BENGKULU - Linsi Oktaviani; Adi Sismanto (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The purpose of this research is based on the identification of the problems stated above, the purpose of this research is to identify whether perceived quality affects the purchase decision of cosmetics in consumers at the My Lova Bengkulu store To identify whether the credibility of the advertisement affects the decision to purchase Wardah cosmetics at the My Lova Bengkulu store. To identify whether the store atmosphere affects the purchase decision of Waedah cosmetics at the My Lova Bengkulu store. This type of research is a quantitative approach. The method used in this study is a descriptive method. Based on the results of this study and the analysis of the data that has been described above, it can be concluded that there is an influence of perceived quality (X2) on the purchase decision of cosmetics (Y) at the My Lova Shop in Bengkulu City, meaning that the higher the perceived quality, the higher the purchase decision. There is an influence of store atmosphere (X2) on the purchase decision of Wardah (Y) cosmetics at Toko My Lova Kota Bengkulu, meaning that the higher the store atmosphere, the higher the purchase decision. There is an effect of perceived quality (X1) and store atmosphere (X2) together or simultaneously on cosmetic purchase decisions (Y). Keywords : Perceived Quality, Store Atmosphere, Purchase Decision.